An Empirical Analysis of IPO Underpricing in China: New Evidence from A-Share Market (2006-2012) - Chen, Si (2013)
This paper undertakes an empirical research on the phenomenon of IPO underpricing in Chinese A-share market, with a sample including 1117 IPOs during the period between 2006 and 2012. This study carries out two methodologies in order to respectively investigate the factors of IPO underpricing in two different aspects. Firstly, the dissertation uses ANOVA through SPSS 19 to analyses the influence of IPO mechanism transition on the degree of IPO underpricing. In this part, the paper uses the sample of all A-shares from 1991 to 2012, including 2539 observations. The result demonstrates that the evolutions in both regulation system and pricing system have profound influences on IPO underpricing magnitude. Secondly, the paper undertakes a multiple regression model through STATA 12 to analyses other influential factors of the magnitude of IPO underpricing. In this model, the sample contains IPO shares after Equity Division Reform, which comprises of 1117 IPOs in Chinese A-share market from 2006 to 2012. The initial return of new shares is used to represent the level of underpricing. Based on previous literatures and features of Chinese stock market, the regression model is created with 11 independent variables, consisting of offering size, offering price, earnings per share, agency cost, the time interval between the issuing day and listing day, turnover rate, lottery rate, circulation rate, IPO system reform in 2009, offering P/E ratio as well as asset-liability rate. According to the empirical result, the 6 variables of offering price, agency cost, turnover rate, lottery rate, IPO system reform and offering P/E ratio are significant determinants to affect the initial return of IPO shares in Chinese brand new market. Besides, the remaining five variables are insignificant related to underpricing degree of new shares.